Emerging Designs of Activatable Photoacoustic Probes for Molecular Imaging - Miao, Qingqing (2017)
Photoacoustic (PA) imaging as a new hybrid imaging modality holds great promise for real-time in vivo monitoring of biological processes with deep tissue penetration and high spatial resolution. To endow PA imaging with the ability to provide real-time molecular information at disease sites, molecular probes that can change their PA signals responding to the target or event of interest have to be developed. This review focuses on the recent development of smart activatable PA probes for molecular imaging. A brief summary of PA imaging agents is given first, followed by the detailed discussion of the contemporary design approaches toward activatable PA probes for different imaging applications. At last, the current challenges are highlighted.